(untitled) (El Hilo de la Fabula, 2024)
This article aims to analyse the elements linked to the formative novel in the Elena Ferrants’s neapolitan tetratology that includes the works: My Brilliant Friend (2011), The Story of a New Name (2012), Those who Leave and Those who Stay (2013) and The Story of the Lost Child (2014). The trajectories of the protagonists of the neapolitan tetratology linked to the literary tradition of what was called the female development novels will be explored with the purpose of identifying the twists and narrative resources that show a break with the female heroines analysed in the 20th century. The purpose of identifying the formal aspects related to the process of formation of female subjects in Ferrante’s work is linked to the relevance of her proposal, which subverts the models analysed by feminist literary criticism of the seventies and that raises discussions related to the feminist debates of the 21st century.